Plasma sIL-2Rα levels are associated with disease progression in myelofibrosis with JAK2V617F but not CALR mutation. (March 2020) - Barosi, Giovanni; Campanelli, Rita; Catarsi, Paolo; De Amici, Mara; Abbà, Carlotta; Viarengo, Gianluca; Villani, Laura; Gale, Robert P.; Rosti, Vittorio; Massa, Margherita
Highlights: More than 50 % of patients with PMF have elevated levels of plasma sIL2-Rα. PMF patients with elevated levels of sIL-2Rα and JAK2 V 617F have an increased risk of disease progression. PMF patients with elevated levels of sIL-2Rα and CALR mutation do not have increased risk of disease progression. These results indicate different pathogenetic mechanisms between JAK2 V617F and CALR mutants PMF.